On visible homelessness and the micro-aesthetics of public space - Young, Alison (The Australian and New Zealand journal of criminology, 2019)
In this article, we investigate the circumstances that have produced the current municipal regulatory approach to homelessness in the City of Melbourne, Victoria, and the ways in which visibly homeless people are policed through a micro-aesthetics of their presence in public space, which involves the monitoring of their bodily demeanour and their physical possessions. Our study contributes to and draws from a range of debates, including studies of the governmental conjunction of poverty and crime, analysis of the co-implication of law and spatiality, research on the criminalisation of homelessness and homeless people, and the burgeoning criminological interest in the significance of the visual field for our understandings of crime and criminality. This article recounts how homelessness, public space and questions of aesthetics have recently coalesced in debates about the regulation of homelessness in the public space of Melbourne’s city centre. It approaches the issues through comparative consideration of genres of municipal management frameworks in other jurisdictions, detailed textual consideration of the Protocol on Homelessness in the City of Melbourne and an empirical study of visible homelessness in the public places of central Melbourne.